RELIABILITY ANALYSIS OF MAIN ROTOR EC 155B1 ON PIN BLADE AND ATTACH BEAMS COMPONENTS USING MARKOV ANALYSIS - Aditiya, Irvan; Pinandhita, Lazuardy Rahendra; Adiputra, Bangga Dirgantara (Vortex, 2022)
Reliability is used to estimate the conditions of systems or components in the future based on previous conditions. The objects of this research are EC 155B1 aircrafts owned by Indonesia Air Transport & Infrastrucure (IAT), and the method used for analysis is markov analysis. Markov analysis is widely used as an analyzing technique the states of the system that has limited information (memoryless). From this research, ATA chapter 62 Main Rotor that meets the requirements of reliability analysis. The constituent components of main rotor states are Pin Blade, Lower Attach Beam, and Upper Attach Beam. The results of the markov analysis of main rotor system, the states that worked properly are state 1, state 3, and state 4. The probability of the state 1 showed that state has decreased from initial condition, while the state 3 and state 4 have increased from initial condition and subsequently have decreased. The reliability of main rotor system has decreased along with increasing of flight hours with the Mean Time To Failure (MTTF) is 2340.22 flight hours.